EFEKTIVITAS MODEL PEMBELAJARAN INKUIRI BERBASIS MEDIA KONKRET TERHADAP KOMPETENSI PENGETAHUAN IPAS SISWA DI KELAS V - Utama Diyatmika; Andi Wapa (Biro 3 Kemahasiswaan dan Kerjasama Universitas Abduracman Saleh Situbondo, 2026)
This research aims to determine the effect of the inquiry learning model assisted by concrete media on the science and science knowledge competency of fifth grade students at SD Negeri Gugus 4, Karangasem District, academic year 2025/2026. This type of research is a quasi-experiment with a research design that is a non-equivalent group design. The population in this study was all class V students at Gugus 4 State Elementary School, Karangasem District, totaling 291 people. The sample was determined using random sampling technique. The sample in this study was class V of SD Negeri 6 Karangasem, totaling 38 people as the experimental group and class V of SD Negeri 9 Karangasem, totaling 32 people as the control group. Data collection was carried out using a test method in the form of a regular multiple choice type objective test. The data obtained was analyzed using the t-test. Based on the results of the t-test analysis, tcount = 6.695 and ttable = 2.000 at a significance level of 5% with dk = 68. Because tcount 6.695 > ttable 2.000, H0 is rejected and Ha is accepted. So it can be stated that there is a significant difference in science knowledge competency between the group of students taught through the inquiry learning model assisted by concrete media and the group of students taught through conventional learning. The average science knowledge competency obtained among the experimental group was higher than that of the control group students (81.55>70.67). So it can be concluded that the inquiry learning model assisted by concrete media has an influence on the science and science knowledge competency of fifth grade students at SD Negeri Gugus 4, Karangasem District, Academic Year 2025/2026.